Remittances in Asia: Implications for the Fight against Poverty and the Pursuit of Economic Growth - Carlos Vargas-Silva; Shikha Jha; Guntur Sugiyarto (Asian Development Bank (ADB), 2009)
This study examines the potential of remittances for promoting economic growth and reducing poverty in Asian countries using data for more than 20 countries in the region for 1988–2007. The results indicate that remittances positively affect home country real gross domestic product (GDP) per capita growth. A 10% increase in remittances as a share of GDP leads to a 0.9–1.2% increase in GDP growth. The findings also show that remittances only have a negligible effect on the overall poverty rate, but they tend to decrease the poverty gap and thereby ameliorate the depth of poverty. The estimates suggest that a 10% increase in remittances decreases the poverty gap by about 0.7–1.4%. The paper also explores the robustness of the key results by using 5-year average data and addresses potential endogeneity issues through instrumental variable estimation.
hdl:11540/1844
Keywords: 330; Migration; Remittances; Poverty; Economic Growth; Impacts